Potential Threats to Indonesia Due to the Granting of Permanent Residence Permits to Mixed Marriage Couples in North Jakarta - Ronauli, Yulita (Security Intelligence Terrorism Journal (SITJ), 2025)
This study seeks to examine the potential risks Indonesia may face as a result of granting Permanent Stay Permits to couples in mixed marriages in North Jakarta. This issue has gained importance due to the rising number of Permanent Stay Permit applications from mixed marriage couples, with Indonesian citizens acting as sponsors. Furthermore, there are concerns that this policy could pose a threat to national security, necessitating a thorough analysis of its potential impacts. The research employs a descriptive qualitative approach, utilizing threat and vulnerability analysis theory by Hank J. Prunckun to assess the risks associated with granting Permanent Stay Permits to mixed marriage couples. To support a detailed data analysis, the study also utilizes ATLAS.ti 9 software, which enables the systematic and efficient organization, extraction, and evaluation of qualitative data. The findings indicate that the lack of data integration within the immigration system hinders comprehensive background checks on foreign nationals married to Indonesian citizens. This raises concerns, as the absence of such checks could create future security risks, particularly in light of the “selective policy” that aims to allow only foreigners who benefit Indonesia without compromising its security. Based on these results, the study recommends implementing the Prevention, Preparedness, Response, and Recovery (PPRR) strategy to enhance the safety and accuracy of the policy. The PPRR approach would help balance the facilitation of rights for mixed-marriage couples while protecting national security, allowing Indonesia to remain welcoming to beneficial foreign nationals while staying vigilant against potential threats. Therefore, intelligence plays a crucial role in addressing potential risks arising from the issuance of Permanent Stay Permits to mixed marriage couples in North Jakarta.